2017
DOI: 10.1128/aac.02509-16
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Thiacetazone Derivatives Active against Mycobacterium abscessus Involves Mutations in the MmpL5 Transcriptional Repressor MAB_4384

Abstract: Available chemotherapeutic options are very limited against Mycobacterium abscessus, which imparts a particular challenge in the treatment of cystic fibrosis (CF) patients infected with this rapidly growing mycobacterium. New drugs are urgently needed against this emerging pathogen, but the discovery of active chemotypes has not been performed intensively. Interestingly, however, the repurposing of thiacetazone (TAC), a drug once used to treat tuberculosis, has increased following the deciphering of its mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 57 publications
(74 reference statements)
10
82
1
Order By: Relevance
“…In addition, inhibitors of energy metabolism may prove highly suitable in drug combination regimens due to interference with drug efflux (53). Efflux pumps have emerged recently as important determinants in drug resistance mechanisms in M. tuberculosis (41,42), as well as in M. abscessus (7). Because a sufficiently high proton motive force and ATP levels have to be maintained for drug extrusion mechanisms, draining the energy supply of efflux pumps may represent an alternative strategy to impede drug efflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, inhibitors of energy metabolism may prove highly suitable in drug combination regimens due to interference with drug efflux (53). Efflux pumps have emerged recently as important determinants in drug resistance mechanisms in M. tuberculosis (41,42), as well as in M. abscessus (7). Because a sufficiently high proton motive force and ATP levels have to be maintained for drug extrusion mechanisms, draining the energy supply of efflux pumps may represent an alternative strategy to impede drug efflux.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed that TB drug discovery platforms could easily be exploited to screen for M. abscessus-active compounds. This led, for instance, to the identification of a piperidinol-based compound (6) or thiacetazone (TAC) derivatives (7), which exhibit potent activity against M. abscessus. However, the quest for discovering potent novel active drugs against M. abscessus could also rely on repurposing TB drugs.…”
mentioning
confidence: 99%
“…C). These mutations in TetR resulted in high induction levels of the mmpS5 and mmpL5 transcripts (Halloum et al ., ). Compellingly, over‐expression of mmpS5/mmpL5 in these resistant mutants did not result in cross‐resistance to any other antibiotics utilised to treat M. abscessus infections, highlighting the specificity toward the compound exported.…”
Section: Introductionmentioning
confidence: 97%
“…Mutations of the mmpS5/mmpL5 operon were associated with resistance to bedaquiline and clofazimine in M. intracellulare and to thiacetazone in M. abscessus [159,160]. Further research may also reveal roles for other efflux pumps of NTM, such as the mmpL gene, in antibiotic resistance.…”
Section: Natural Antibiotic Resistancementioning
confidence: 95%
“…MmpLs belongs to the resistance-nodulation-cell division permease superfamily [157]. Since Pasca and colleague [158] first reported that the mmpL7 gene from M. tuberculosis conferred resistance to isoniazid when overexpressed in M. smegmatis, orthologs of mmpL and mmpS genes have been characterized and identified in NTM [159].…”
Section: Natural Antibiotic Resistancementioning
confidence: 99%